MARKETING CAMPAIGN PERFORMANCE MEASUREMENT: A MANAGEMENT ACCOUNTING APPROACH - Loso Judijanto; Oskar Hutagaluh (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Marketing campaign performance measurement is important for companies to assess the effectiveness of their marketing strategies. The management accounting approach offers a more thorough way to measure and analyse the impact of marketing activities. This method combines financial and non-financial measures to provide a more complete picture of marketing campaign results. Companies can use various measurement tools such as Return on Marketing Investment (ROMI), cost of acquiring a new customer, and lifetime customer value. These tools help companies see not only the short-term results, but also the long-term benefits of their marketing investments. This approach also helps companies make better use of resources and make more informed decisions. By using a management accounting approach, companies can more accurately assess their marketing campaigns. It also helps bring marketing and finance teams together, creating a common way to measure and report results. Ultimately, the use of this approach can help companies better understand and improve the impact of their marketing campaigns, which can improve overall business performance.